2014
DOI: 10.21109/kesmas.v8i8.413
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Ibu dalam Memberikan Pendidikan Seksualitas pada Remaja Awal

Abstract: Akumulasi kasus HIV/AIDS di Provinsi Jawa Tengah, tahun 1993 - 2008 adalah pada usia 20 - 24 tahun sekitar 12,54% dan usia 25 - 29 tahun sekitar 37,31% merupakan kategori remaja dan dewasa muda. Di Kabupaten Magelang kasus HIV positif pada remaja mulai muncul tahun 2008 dan selalu muncul pada tahun berikutnya. Remaja sangat membutuhkan informasi tentang seksualitas dan peran ibu sangat penting. Tujuan penelitian ini adalah untuk mengetahui determinan perilaku ibu yang meliputi umur, pekerjaan, pendidikan, peng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
14
Order By: Relevance
“…Teenagers who have an open communication with parents, especially on reproductive health have a tendency not have sexual relations before marriage. In addition, the limitations of parental knowledge about reproductive health and sexuality also to be a barrier for parents to provide information about sexuality to their children (Dessie, 2015;Keijsers 2010;Meilani, 2014;Sohn, 2012) Finally, most adolescents are still reluctant to discuss sexuality with their parents. Results of research conducted by Widyastari, et al showed 54.2% of adolescents who do not get enough information about reproductive health and sexuality are reluctant to discuss sexuality with their parents.…”
Section: Resultsmentioning
confidence: 99%
“…Teenagers who have an open communication with parents, especially on reproductive health have a tendency not have sexual relations before marriage. In addition, the limitations of parental knowledge about reproductive health and sexuality also to be a barrier for parents to provide information about sexuality to their children (Dessie, 2015;Keijsers 2010;Meilani, 2014;Sohn, 2012) Finally, most adolescents are still reluctant to discuss sexuality with their parents. Results of research conducted by Widyastari, et al showed 54.2% of adolescents who do not get enough information about reproductive health and sexuality are reluctant to discuss sexuality with their parents.…”
Section: Resultsmentioning
confidence: 99%
“…Sangat disayangkan, bahwa orang sekitar terutamanya orang tua, kurang membantu menunjang pemahaman terhadap masalah seksual remaja. Demikian pula di sekolah, lembaga pendidikan formal juga kurang memberikan pendidikan seksual secara memadai bagi remaja (Meilani, Shaluhiyah, & Suryoputro, 2014).…”
Section: Pendahuluanunclassified
“…Hal tersebut juga tertuang dalam program pemerintah dalam Bina Keluarga Remaja. Sekolah dan lingkungan dapat menjadi wahana dalam menciptakan sikap positif remaja melalui kegiatan Pusat Informasi dan Konseling Kesehatan 8,10 Reproduksi Remaja (PIK KRR).…”
Section: Pembahasanunclassified